2018
DOI: 10.1063/1.5051584
|View full text |Cite
|
Sign up to set email alerts
|

Improved thermal stability in doped MnN/CoFe exchange bias systems

Abstract: We investigated the influence of doping antiferromagnetic MnN in polycrystalline MnN/CoFe exchange bias systems, showing high exchange bias of up to 1800 Oe at room temperature. The thermal stability of those systems is limited by nitrogen diffusion that occurs during annealing processes. In order to improve the thermal stability, defect energies of elements throughout the periodic table substituting Mn were calculated via density functional theory. Elements calculated to have negative defect energies bind nit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
3
3
0
Order By: Relevance
“…Possibly, those samples exhibit a maximum of exchange bias at temperatures T A > 550 • C, followed by a collapse, that might also be shifted to higher temperatures. The minimum of exchange bias marking the transition from temperature range I to II has also been observed in all our previous studies on MnN exchange bias systems [10,12,19]. At this point we are not sure what causes this behavior, but it is likely that a magnetic ordering transition is happening at annealing temperatures around T A = 250 • C. The fact that all samples show similar values of exchange bias in the first regime could hint at the formation of a spin glass structure in the MnN [21,22].…”
Section: A Ta Thickness Variationsupporting
confidence: 80%
See 2 more Smart Citations
“…Possibly, those samples exhibit a maximum of exchange bias at temperatures T A > 550 • C, followed by a collapse, that might also be shifted to higher temperatures. The minimum of exchange bias marking the transition from temperature range I to II has also been observed in all our previous studies on MnN exchange bias systems [10,12,19]. At this point we are not sure what causes this behavior, but it is likely that a magnetic ordering transition is happening at annealing temperatures around T A = 250 • C. The fact that all samples show similar values of exchange bias in the first regime could hint at the formation of a spin glass structure in the MnN [21,22].…”
Section: A Ta Thickness Variationsupporting
confidence: 80%
“…In the course of our previous investigations [10] we already found that preparing MnN with a higher nitrogen concentration can * mdunz@physik.uni-bielefeld.de slightly increase the thermal stability but at the same time lowers the exchange bias. Similar results are obtained when doping MnN with elements that have stronger bonds with nitrogen [19].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the spin orientation is controversial and might depend critically on the lattice constants. In previous studies, some of the authors of this article have shown its utility for exchange bias applications with large exchange bias fields at room temperature [22][23][24][25][26][27]. However, the critical thickness for the onset of exchange bias was observed to be around 10 nm at room temperature, leading to the conclusion that MnN has a small magnetocrystalline anisotropy energy density [22].…”
Section: Introductionmentioning
confidence: 99%
“…Doping has been shown to enhance the thermal stability of MnN/CoFe exchangebias systems [19]. Undoped samples with structure Ta(10 nm)/MnN(30 nm)/Co 70 Fe 30 / (1.6 nm)/Ta(0.5 nm)/Ta 2 O 5 (5 nm) were deposited on thermally oxidized Si wafers.…”
Section: Exchange Bias: In-plane Studiesmentioning
confidence: 99%